2016
DOI: 10.1002/smll.201603070
|View full text |Cite
|
Sign up to set email alerts
|

Local Effects on Airway Inflammation and Systemic Uptake of 5 nm PEGylated and Citrated Gold Nanoparticles in Asthmatic Mice

Abstract: Nanotechnology is showing promise in many medical applications such as drug delivery and hyperthermia. Nanoparticles administered to the respiratory tract cause local reactions and cross the blood-air barrier, thereby providing a means for easy systemic administration but also a potential source of toxicity. Little is known about how these effects are influenced by preexisting airway diseases such as asthma. Here, BALB/c mice are treated according to the ovalbumin (OVA) asthma protocol to promote allergic airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Omlor et al. developed an ICP‐MS method for the investigation of the biodistribution of PEGylated gold nanoparticles in different tissues [161]. The ICP–MS quantitative analysis results indicated that the uptake of PEGylated gold nanoparticles was higher than citrated gold nanoparticles.…”
Section: Bioanalytical Methods For Polyethylene Glycols and Pegylatedmentioning
confidence: 99%
“…Omlor et al. developed an ICP‐MS method for the investigation of the biodistribution of PEGylated gold nanoparticles in different tissues [161]. The ICP–MS quantitative analysis results indicated that the uptake of PEGylated gold nanoparticles was higher than citrated gold nanoparticles.…”
Section: Bioanalytical Methods For Polyethylene Glycols and Pegylatedmentioning
confidence: 99%
“…In the OVA asthma model, Au NPs have been found to actually decrease OVA-induced allergy as seen by decreased inflammatory cell lung accumulation, decreased mucus production and lower cytokine levels (Barreto et al, 2015). Similarly, both PEGylated and citrated Au NPs have been shown to attenuate OVA-induced inflammation: both types of Au NPs decreased AHR, total BALF cell counts and eosinophil numbers (Omlor et al, 2017). This study also examined extrapulmonary uptake of Au NPs, finding that asthmatic mice had more NPs deposited in the spleen.…”
Section: Gold Nanoparticlesmentioning
confidence: 96%
“…In the OVA asthma model, Au NPs have been found to actually decrease OVA-induced allergy as seen by decreased inflammatory cell lung accumulation, decreased mucus production and lower cytokine levels [34]. Similarly, both PEGylated and citrated Au NPs have been shown to attenuate OVA-induced inflammation: both types of Au NPs decreased AHR, total BALF cell counts and eosinophil numbers [35]. This study also examined extrapulmonary uptake of Au NPs, finding that asthmatic mice had more NPs deposited in the spleen [35].…”
Section: Enm-induced Asthma Exacerbationsmentioning
confidence: 99%
“…Similarly, both PEGylated and citrated Au NPs have been shown to attenuate OVA-induced inflammation: both types of Au NPs decreased AHR, total BALF cell counts and eosinophil numbers [35]. This study also examined extrapulmonary uptake of Au NPs, finding that asthmatic mice had more NPs deposited in the spleen [35]. The effects of the protein corona (that is, the proteins that adsorb to the surface of NPs) on Au NP toxicity have been examined by conjugating Au NPs with coronas of common allergens, and Au NPs conjugated with the allergen Der p 1, which is a component of house dust mite, enhanced its protease activity and increased basophil activation in in vitro assays, suggesting that co-exposures of allergens with NPs could enhance inflammation in asthma through corona formation [36].…”
Section: Enm-induced Asthma Exacerbationsmentioning
confidence: 99%